Yak rumen microbial diversity at different forage growth stages of an alpine meadow on the Qinghai-Tibet Plateau - Ma,Li; Xu,Shixiao; Liu,Hongjin; Xu,Tianwei; Hu,Linyong; Zhao,Na; Han,Xueping; Zhang,Xiaoling (PeerJ, 2019)
The rumen microbiota of ruminants plays a vital role in fiber digestion, and environmental factors affect its community structure. The yak (Bos grunniens) is the main livestock species that inhabits the Qinghai-Tibet Plateau (QTP) at regions located at high-altitude of 3,000–5,000 m. This work investigated the rumen bacterial community of yak that grazed on the QTP during the whole year to evaluate the relationship between the rumen bacterial community and the nutrient composition of forage plant at three stages. In this study, the diversity of the rumen prokaryotic community composition was monitored in 10 full-grazing yak in an alpine meadow of the QTP. The nutrient composition of three forage growth stages was determined: re-green stage (REGY), grassy stage (GY), and withered stage (WGY). High-throughput sequencing of bacterial 16S rRNA gene was used. The results showed that the nutritive composition of the alpine meadow changed with the seasons: crude protein (CP) (13.22%) was high in forage during REGY (spring), while neutral detergent fiber (NDF) (59.00%) was high during WGY (winter). Microbial diversity and richness were highest during REGY and the average number of operational taxonomic units from 30 samples was 4,470. The microbial composition was dominated by members of Bacteroidetes (51.82%), followed by Firmicutes (34.08%), and the relative microbial abundance changed in the three forage growth stages. Unweighted UniFrac distance PcoA showed that the bacterial community structure differed between REGY, GY, and WGY. Furthermore, taxonomic groups did not present differences regarding gender in these three stages. The rumen microbiota was enriched with functional potentials that were related to ABC transporters, the two-component system, Aminoacyl-tRNA biosynthesis, and metabolism of Purine, Pyrimidine, Starch and sucrose metabolism. Significant differences were found in the composition, diversity, and function of yak ruminal microorganisms during different forage growth stages. This indicates that microbial changes in the rumen depend on changes in the forage nutritional composition. These findings provide evidence on the rumen microbial diversity of yaks in the QTP.
Keywords: Microbial composition; Rumen microbiota; Yak; Forage nutritional composition; Function; Qinghai-Tibet Plateau; Different forage growth stages